The NV0 defects in diamond: A quantum mechanical characterization through its vibrational and Electron Paramagnetic Resonance spectroscopies. (January 2022) - Ferrari, Anna Maria; D'Amore, Maddalena; El-Kelany, Khaled E.; Gentile, Francesco Silvio; Dovesi, Roberto
Abstract: The NV 0 defect in diamond has been investigated quantum-mechanically, by analyzing its structural, electronic, vibrational and magnetic properties. The possible spin states for NV 0 are a quartet N V q 0 ( 4 A 2 symmetry) and a doublet ( 2 E symmetry). In the latter state a single electron occupies a double degenerate level producing a Jahn Teller distortion that removes the degeneracy and lowers the total energy. The symmetry reduces from C 3 v to C S and two local minima are indeed identified, to be indicated as N V d 1 0 ( 2 A ′ symmetry) and N V d 2 0 ( 2 A ″ symmetry). N V d 1 0 is the ground state, and is more stable than N V q 0 by ~ 0.5 eV, and than N V d 2 0 by ~ 0.2 eV, irrespective of the functional or basis set adopted. The EPR hyperfine coupling tensor has been computed for N V q 0 and has been found to be in excellent agreement with available experimental data. The IR spectra of the NV defects (the three neutral cases and also the negatively charged one, for comparison) show specific peaks and shape that characterize each system and differentiate the spectra according to the spin and charge state. The Raman spectra of the NV 0 defects shows a single peak, redshifted with respect to the single peak of pristine diamond by 2 cm −1 only, but in turn well separated from the negatively charged form of the defect. Graphical abstract: Image 1 Highlights: NV 0 defect consist of a substitutional Nitrogen adjacent to a carbon vacancy. The defect in its neutral charge state has been investigated quantum-mechanically. EPR hyperfine coupling tensors have been calculated. IR spectra of NV defects (in different spin and charge states) show specific peaks.